The Eight Books : A Complete English Translation - Sepehri, Sohrab (Brill, 2021)
The Eight Books: A Complete English Translation is the first complete translation of the collected poems of Sohrab Sepehri (1928-1980), a major Iranian modernist poet and painter and yet under-translated into English. The introduction takes up Sepehri's famously difficult if languidly beautiful style to explain it as a series of appropriations of global modernisms in poetry and painting. It offers close readings of how Sepehri's modernism follows and breaks with the jagged rhythms of Nima Yushij (d.1960), Iran's inaugural modernist poet. In keeping with this modernist framing, the translations replicate Sepehri's rhymes where possible, his fluctuations between formal and colloquial registers, his syntactic distortions, and his embeddings of governmental and other jargons. It also includes Sepehri's autobiography.